Rheological behavior of a novel fracturing fluid formed from amine oxide surfactants. Issue 5 (30th May 2022) - Chen, Jing; Tan, Xinyuan; Fang, Bo; Liu, Boxiang; Gao, Hang; Li, Kejing; Yu, Luyao; Xu, Ke; Lu, Yongjun; Qiu, Xiaohui
Abstract: In this paper, two kinds of long‐chain amine oxide surfactants, erucamidopropyl dimethylamine oxide (EAOS) and oleamidopropyl dimethylamine oxide (OAOS) were synthesized and compounded with different mass ratios. The rheological tests show that there is a synergistic effect between EAOS and OAOS, and this effect reaches the strongest at the EAOS/OAOS solution with α  = 0.7 ( α is the mass fraction of EAOS in the mixed surfactant). Through the synergistic effect between EAOS and OAOS, the temperature resistance of amine oxide surfactant solutions can be effectively improved. EAOS/OAOS ( α  = 0.7) solutions with total surfactant mass fractions of 3, 4, and 5 wt% show good high‐temperature resistance at 130, 140, and 150°C, respectively. After shearing for 60 min at 100 s −1, 160°C, the remaining viscosity of the 5 wt% EAOS/OAOS ( α  = 0.7) with 1 wt% KCl solution is 30 mPa s, meeting the demand of viscoelastic surfactant fracturing fluids.